Asymmetric Mannich Reaction of N-Boc Imines with Alkylmalononitriles Catalyzed by Dinuclear PhosphoiminoBINOL-Pd Complex - Arai, Takayoshi; Nakamura, Ayu (Synlett, 2019)
PhosphoiminoBINOL-Pd2(OAc)2 complex catalyzed asymmetric Mannich reaction of N-Boc imines with alkyl malononitriles, with assistance of Zn(OAc)2 gave chiral amines with adjacent all-carbon quaternary carbon centers in up to 99% yield with 94% ee.
Keywords: Mannich; asymmetric catalyst; chiral amine; quaternary carbon center